EVALUASI PENERAPAN SISTEM E-FAKTUR 3.0 DALAM MELAPORKAN SPT MASA PPN PADA CV. MAYIBA AGUNG MANDIRI KOTA SORONG-PAPUA BARAT - Sahetapy, Tirsha Cindy; Runtu, Treesje; Tangkuman, Steven J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
E-Faktur version 3.0 is one of the efforts to improve the tax administration system which aims to improve taxpayer compliance in paying taxes but also to create security and convenience in the tax administration process, especially Value Added Tax. This study aims to determine the application of the e-Faktur 3.0 system in reporting the VAT period SPT and to determine the reporting of the VAT period SPT before and after implementing the 3.0 e-Faktur system on CV. Mayiba Agung Mandiri, Sorong City, West Papua. The analytical method used in this research is descriptive analysis method. The results of the study stated that CV. Mayiba Agung Mandiri has implemented e-Faktur 3.0 in reporting the VAT period SPT, where the results are more effective because it is simple and short when compared to the previous version of e-Faktur. In addition, in the application of e-Faktur 3.0, the Input Tax Invoice has not been fully carried out by CV. Mayiba Agung Mandiri, because of the small purchase value and transaction made with non-PKP.